The risks of prolonged use of hormonal contraceptives (Research, Society and Development, 2020)
Contraceptive methods majorly are used to prevent pregnancy. Concerning the frequent use of hormonal contraceptive methods, several studies show that prolonged use may cause harm to women's health. The present work aims to describe the main types of hormonal contraceptives, address the action mechanisms of each method, and to describe the emergence of pathologies related to their prolonged use. The study is a qualitative literature review with an exploratory character. Contraceptives have an important role concerning the liberty of women in deciding when to start a pregnancy. However, its use should be dependent on the advice of a specialist, since there are particularities that must be analyzed to promote the use of the most suitable drug.